Identification, Classification, and Expression Analysis of GRAS Gene Family in Malus domestica - Fan, Sheng; Zhang, Dong; Gao, Cai; Zhao, Ming; Wu, Haiqin; Li, Youmei; Shen, Yawen; Han, Mingyu (Frontiers in Physiology, 2017)
GRAS genes encode plant-specific transcription factors that play important roles in plant growth and development. However, little is known about the GRAS gene family in apple. In this study, 127 GRAS genes were identified in the apple (Malus domestica Borkh.) genome and named MdGRAS1 to MdGRAS127 according to their chromosomal locations. The chemical characteristics, gene structures and evolutionary relationships of the MdGRAS genes were investigated. The 127 MdGRAS genes could be grouped into eight subfamilies based on their structural features and phylogenetic relationships. Further analysis of gene structures, segmental and tandem duplication, gene phylogeny and tissue-specific expression with ArrayExpress database indicated their diversification in quantity, structure and function. We further examined the expression pattern of MdGRAS genes during apple flower induction with transcriptome sequencing. Eight higher MdGRAS (MdGRAS6, 26, 28, 44, 53, 64, 107 and 122) genes were surfaced. Further quantitative reverse transcription PCR indicated that the candidate eight genes showed distinct expression patterns among different tissues (leaves, stems, flowers, buds and fruits). The transcription levels of eight genes were also investigated with various flowering related treatments (GA3, 6-BA and sucrose) and different flowering varieties (Yanfu No.6 and Nagafu No.2). They all were affected by flowering-related circumstance and showed different expression level. Changes in response to these hormone or sugar related treatments indicated their potential involvement during apple flower induction. Taken together, our results provide rich resources for studying GRAS genes and their potential clues in genetic improvement of apple flowering, which enriches biological theories of GRAS genes in apple and their involvement in flower induction of fruit trees.